2022
DOI: 10.1155/2022/4351282
|View full text |Cite|
|
Sign up to set email alerts
|

What Promotes Medical Overuse: Perspective on Evolutionary Game between Administration and Medical Institutions

Abstract: Medical overuse is the leading cause of high expenditure among healthcare systems worldwide, with the degree varying from region to region. There is increasing evidence to indicate that in China, National Healthcare Security Administration (NHSA) supervision plays the most crucial role in decreasing medical overuse. For medical overuse, traditional studies focus on empirical researches and qualitative analysis, most of which ignore how the two important participants, i.e., medical institutions and NHSA, affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Usually, government departments do not directly supervise the daily operation of medical institutions [ 28 ]. Due to the large number of medical institutions in China, the operation of the regulatory mechanism requires a large workforce, material resources, and financial resources [ 29 ], and there are no low regulatory costs. The income and development of medical institutions bring “income generation” to government departments.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, government departments do not directly supervise the daily operation of medical institutions [ 28 ]. Due to the large number of medical institutions in China, the operation of the regulatory mechanism requires a large workforce, material resources, and financial resources [ 29 ], and there are no low regulatory costs. The income and development of medical institutions bring “income generation” to government departments.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%